2018
DOI: 10.1038/s41422-018-0086-7
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate kinase M2 regulates homologous recombination-mediated DNA double-strand break repair

Abstract: Resistance to genotoxic therapies is a primary cause of treatment failure and tumor recurrence. The underlying mechanisms that activate the DNA damage response (DDR) and allow cancer cells to escape the lethal effects of genotoxic therapies remain unclear. Here, we uncover an unexpected mechanism through which pyruvate kinase M2 (PKM2), the highly expressed PK isoform in cancer cells and a master regulator of cancer metabolic reprogramming, integrates with the DDR to directly promote DNA double-strand break (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 47 publications
4
52
0
Order By: Relevance
“…We previously reported that PKM2 is upregulated and suggested that it functions as a tumor promoter in human CC [12]. More importantly, it has been found that downregulation of PKM2 effectively enhances radiosensitivity in human non-small-cell lung carcinoma [10, 27] and glioblastoma multiforme cell lines (U87, T98G, and U251) [28]. As anticipated, our results showed that high PKM2 expression was related to clinical radioresistance in patients with CC.…”
Section: Discussionsupporting
confidence: 81%
“…We previously reported that PKM2 is upregulated and suggested that it functions as a tumor promoter in human CC [12]. More importantly, it has been found that downregulation of PKM2 effectively enhances radiosensitivity in human non-small-cell lung carcinoma [10, 27] and glioblastoma multiforme cell lines (U87, T98G, and U251) [28]. As anticipated, our results showed that high PKM2 expression was related to clinical radioresistance in patients with CC.…”
Section: Discussionsupporting
confidence: 81%
“…Pyruvate kinase isoform M2 (PKM2), the key rate-limiting enzyme catalyzing the final step of glycolysis, plays a critical role in tumor glucose metabolism and is highly expressed in various types of human cancers (9,10). PKM2 has been proposed to play a vital role in maintaining the metabolism program (11,12), promoting proliferation (11), resistance to genotoxic treatments (13), and metastasis (14) and inducing cancer stem-like cell properties (15) in many types of cancer. Besides its roles in regulating the cancer cell, PKM2 has been proven to contribute to tumor microenvironment, such as reducing lactate production, increasing OXPHOS (9,16).…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of functions of moonlighting proteins secondary to catalysis include signal transduction, transcriptional regulation, apoptosis, motility, and structural functions (31). Cytoplasmic enzymes, pyruvate kinase M2 (PKM2) and glyceraldehyde 3-phosphate dehydrogenase (GAPDH), have acquired secondary non-enzymatic roles such as DNA repair protein in the nucleus and RNA-binding protein (12,30), respectively, in addition to the primary enzyme catalytic roles. These proteins with a glycolysis function have common characteristics to form homo-oligomer and their function and localization were known to differ based on their forms (2,8,25,36).…”
Section: Discussionmentioning
confidence: 99%